THE IMPLEMENTATION OF THE BATIMUNG TRADITION IN SAMARINDA ULU DISTRICT, SAMARINDA CITY - Indarto; Kirwanto, Agus; Suhendriyo; Muthiah, Hanun (Jurnal Jamu Kusuma, 2024)
Batimung is a cultural practice that has existed since the Majapahit era and has been preserved by the Banjar community for generations. The implementation of batimung is specifically intended for prospective brides to prevent excessive sweating. Additionally, batimung is also used as a traditional treatment. The research aimed to explore the utilization of batimung for beauty treatments and traditional healing. The research methodology employed was exploratory, using qualitative data collection techniques. The findings of this research include the tradition of batimung as a beauty treatment which was conducted before marriage for prospective couples to collect their sweat. On the other hand, batimung was also practiced as a traditional healing method, aiming for well-being and treatment within the Banjar community. The herbal ingredients used in batimung include lemongrass, pandan leaves, ginger, wood shavings, and fragrances such as rose petals, jasmine flowers, and patchouli leaves. The equipment used in the batimung tradition includes stove, pot, covering cloth, mat, small chair, and stirrer. The procedure of batimung involves removing all clothing first, then wearing a sarong as a covering. The person undergoing batimung then lies on a mat, which has been infused with boiled herbs for approximately 30 minutes. After the batimung process, individuals may receive a massage and body scrub, which is optional. Subsequently, individuals are allowed to take a bath to maximize the effects of the batimung ritual. The purpose and benefits of practicing the batimung tradition were to enhance beauty, traditional healing, eliminate sweat odor, and refresh the body.